Pandemic experiences and psychopathological aspects in individuals with mood disorders and other mental disorders - Del Casale, Antonio; Lai, Carlo; Iannuccelli, Alessia; Ciacchella, Chiara; Veneziani, Giorgio; Ali, Mohamed; Zocchi, Clarissa; Bilotta, Irene; Pompili, Maurizio (Frontiers in Psychiatry, 2022)
Individuals with different personality traits, temperaments, and psychological symptoms have different attitudes toward the pandemic experiences and restrictive measures. The aim of the present study was to evaluate the associations between the psychological factors and the attitudes toward COVID-19, experienced during the third pandemic wave in Italy, in a sample of individuals with psychiatric disorders. Between March and September 2021, 53 patients with mood disorders and other mental disorders completed a survey composed of self-report questionnaires that assessed sleep quality, depressive and hypomanic symptoms, and temperament and personality traits. Positive and negative attitudes toward the pandemic experience were assessed using an ad hoc questionnaire. The results showed that individuals with more severe depressive symptoms were less prone to adhere to government guidelines, and were more convinced that the pandemic was not a real problem. Reduced sleep quality was associated with increased skepticism toward official explanations concerning the causes of COVID-19. Lastly, negative affect and cyclothymic temperament predicted the disposition towards COVID-19 vaccines. In conclusion, these findings highlighted that some psychological aspects and psychiatric symptoms could influence the beliefs about COVID-19 and compliance with government recommendations. Further research is needed to provide indications on how to improve the current healthcare policies.